Part II; Summaries of lectures in the field of physical protection, control and accounting (MPC & A) of nuclear material - Бойко В. И. Владимир Ильич; Степанов Б. П. Борис Павлович; Силаев М. Е. Максим Евгеньевич; Егоров Н. Б. Николай Борисович; Амелина Г. Н. Галина Николаевна (2008, 2008)
Заглавие с титульного экрана